Update on vitamin D status in sunshine-abundant Thailand, 2019–2020 - Chailurkit L.o. (2023)
Objective: The prevalence of vitamin D deficiency worldwide remains unknown. In the Thai 4th National Health Examination Survey (2008–2009) cohort, ∼45% and 7% of the adult population had serum 25-hydroxyvitamin-D [25(OH)D] levels below the threshold of 75 and 50 nmol/L, respectively. Vitamin D has been a hot topic in the scientific community. The aim of this study was to uncover the current situation regarding vitamin D status in Thailand. Methods: Participants were 4098 adults ages 10 to 96 y, randomly selected from the Thai 6th National Health Examination Survey (2019–2020) cohort. Serum 25(OH)D levels were measured by liquid chromatography/tandem mass spectrometry. Data were expressed as mean ± SE and adjusted odds ratio (95% CI). Results: Mean vitamin D status based on serum 25(OH)D was 88.2 nmol/L and differed by age, sex, residency, and religion. The prevalence of serum 25(OH)D <75 and <50 nmol/L were 31% and 4%, respectively. The prevalence of vitamin D deficiency was lower in individuals who lived in the northeastern part of Thailand or were male. The risk for vitamin D deficiency was lower than that in 2009. In multiple linear regression analysis, female sex, younger age, urbanization, a higher body mass index, Muslim religion, and living in Bangkok or the central region of Thailand were independently associated with lower serum 25(OH)D levels. Conclusions: The vitamin D status in the Thai population has improved over the past 10 y. This improvement may reflect an increased awareness related to adequate vitamin D status.